Option-based tasks: an effort to encourage the EFL students to learn - Tono Suwartono; Nina Fivi Oktavia (University of Muhammadiyah Purwokerto, 2019)
Teaching is to create environment for students to learn. However, there are times when students become reluctant to learn. One reason is the given learning tasks are irrational. A good example in the ELT context is a common reading comprehension class in which the teacher gets the students to produce oral or written answers to a series of ‘wh’ questions that follow a reading passage. It is too demanding. This paper aims to propose EFL learning tasks that adopt (or adapt) option-based techniques in an attempt to facilitate students’ learning. The paper begins with the rationale behind the adoption of each technique. Then, it discusses things to consider when preparing the tasks. A selected sample of such techniques for ELT will be presented in the last part of the paper.Keywords : Option-base tasks, ELT, techniques